Learning from direct instruction: Best prepared by several self-regulated or guided invention activities?. (October 2017) - Glogger-Frey, Inga; Gaus, Katharina; Renkl, Alexander
Abstract: Learning from direct instruction can be enhanced by preparatory invention tasks: students invent an index that allows to differentiate a set of cases regarding important aspects (self-regulated). However, contradictory results have been found. As self-regulated activities often need practice, we tested whether the contradictory findings persist when students can practice inventing. We randomly assigned 99 eighth-grade students to two conditions (independent variable): they either invented twice (self-regulated; n = 49) or worked through worked solutions of the two tasks (guided; n = 50) before learning about ratios in physics from a lecture. Extraneous load, deep-structure recall, knowledge-gap perception, and self-efficacy were potential mediators. Transfer was the dependent measure. Guidance led to less extraneous load. However, self-regulation led to higher transfer because the students devoted more attention to the deep structure of the preparation tasks. Our findings suggest that—given some practice—self-regulated outperforms guided preparation for learning from direct instruction. Highlights: Two preparation for future learning phases preceded a lecture and were varied. Either an open inventing (self-regulated) or a worked problem (guided) was given. Self-regulated inventing led to higher transfer, guidance to less extraneous load. Extraneous load mediated far transfer, thus somewhat dampened inventing's advantage. Encoding of problems' deep structure, increased by inventing, mediated far transfer.